2011
DOI: 10.1007/s10549-011-1647-3
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ cytotoxic T cell and FOXP3+ regulatory T cell infiltration in relation to breast cancer survival and molecular subtypes

Abstract: The prognostic significance of tumor-associated FOXP3(+) regulatory T cells (Tregs) and CD8(+) cytotoxic T lymphocytes (CTLs) in invasive breast carcinomas is studied. Tregs and CTLs were assessed by immunohistochemistry in 1270 cases of invasive breast carcinoma for their associations with patient survival, histopathologic features, and molecular subtypes. Infiltrates of Tregs and CTLs were observed within tumor bed and in the tissue surrounding tumor. Within tumor bed, increased infiltration of Tregs and CTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
246
5
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(280 citation statements)
references
References 30 publications
28
246
5
1
Order By: Relevance
“…This increase coincided with a significant increase in the CD8:Treg ratio (Fig. 4J), which has been associated with the sensitivity of a tumor to a given therapy and also with improved overall survival in patients with breast cancer and other cancer subtypes (3,(31)(32)(33). Collectively, these data indicate that directing the CD8 T-cell response using anti-DEC-205/HER2 vaccination enhances the efficacy of combination therapy, reverses Th2 cytokine production by CD4 T cells, and enhances effector CD8 T-cell infiltration into the tumor.…”
Section: Resultsmentioning
confidence: 71%
“…This increase coincided with a significant increase in the CD8:Treg ratio (Fig. 4J), which has been associated with the sensitivity of a tumor to a given therapy and also with improved overall survival in patients with breast cancer and other cancer subtypes (3,(31)(32)(33). Collectively, these data indicate that directing the CD8 T-cell response using anti-DEC-205/HER2 vaccination enhances the efficacy of combination therapy, reverses Th2 cytokine production by CD4 T cells, and enhances effector CD8 T-cell infiltration into the tumor.…”
Section: Resultsmentioning
confidence: 71%
“…In the end, we reviewed 58 studies encompassing 16 different cancer types (Table 1), including bladder (19), breast (21)(22)(23)(24)(25)(26)(27)(28), cervical (29,30), colorectal (12,(31)(32)(33)(34)(35)(36)(37)(38)(39), endometrial (40)(41)(42), gastric (14,(43)(44)(45)(46), head and neck (47), hepatocellular (48)(49)(50)(51)(52), lung (53,54), melanoma (55)(56)(57)(58), mesothelial (59), oral (4,(60)(61)(62)(63), ovarian (2,3,…”
Section: Introductionmentioning
confidence: 99%
“…9,10 However, the relationship between FOXP3+ and outcome has shown diverse results inconsistent with the initial hypothesis. 9,10,[30][31][32][33][34] One study reported that FOXP3+ was only associated with good outcome only in ER− tumors. 30 In this study, FOXP3+ was significantly higher in the response group than in the NR group (p = 0.020), and no differences were observed in CD8+ between the groups (p = 0.474).…”
Section: Discussionmentioning
confidence: 99%